2007
DOI: 10.1080/09595230701247780
|View full text |Cite
|
Sign up to set email alerts
|

Clinical supervision in the alcohol and other drugs field: an imperative or an option?

Abstract: There is a growing interest in Clinical Supervision (CS) as a central workforce development (WFD) strategy. This paper provides a definition of and rationale for CS, characterises its various forms, identifies selection and training issues, and advises on policy and implementation issues central to redressing shortcomings in supervision practice within the alcohol and other drugs (AOD) field. Relevant selective literature is reviewed. Key conceptual issues were identified, and strategies developed to address i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 29 publications
0
34
0
Order By: Relevance
“…This finding may be further compounded in Indigenous workplaces where the workplace culture is less familiar with supervision . Previous research has demonstrated the importance of clinical supervision in minimising emotional exhaustion and turnover in AOD workers (Knudsen et al, 2008;Roche et al, 2007).…”
Section: Workforce Representationmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may be further compounded in Indigenous workplaces where the workplace culture is less familiar with supervision . Previous research has demonstrated the importance of clinical supervision in minimising emotional exhaustion and turnover in AOD workers (Knudsen et al, 2008;Roche et al, 2007).…”
Section: Workforce Representationmentioning
confidence: 99%
“…Non-Indigenous workers reported experiencing pressure from different types of clients, particularly manipulative, poly-drug using, and demanding clients. Greater training and support in the form of clinical supervision (Knudsen, Ducharme, & Roman, 2008;Roche, Todd, & O'Connor, 2007;Health Workforce Australia, 2010) may help workers manage pressures they face from difficult clients.…”
Section: Emotional Exhaustionmentioning
confidence: 99%
“…For example, some studies show positive links between clinical supervision and professional development (Butterworth, Bell, Jackson, & Pajnkihar, 2008;Martino, Ball, Nich, Frankforter, & Carroll, 2008;Roche, Todd, & O'Connor, 2007), as well as decreased intent to leave and decreased burnout of workers (Begat & Severinsson, 2006;Hyrkas, Appelqvist-Schmidlechner, & Haataja, 2006). However findings from clinical supervision studies have been mixed, with some reports that supervisees have perceived clinical supervision to be ineffective for their practice (e.g.…”
Section: Introductionmentioning
confidence: 88%
“…High quality clinical supervision has been linked to positive benefits for clinicians, clients and organisations (Edwards et al, 2006;Roche et al, 2007). Hence, within Australia there has been a national drive to implement clinical supervision across public health services (Health Workforce Australia, 2010).…”
Section: ) There Is a Need To Establish The Effectiveness Of Clinicamentioning
confidence: 99%
See 1 more Smart Citation